Optimasi Gigabit Passive Optical Network dan Algoritma Naïve Bayes dalam Analisis Jaringan FTTH - Suwandi,; Akbar, Yuma; Mulyana, Dadang Iskandar (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Internet service users expect reliable bandwidth quality to support the communication access process. From year to year, human needs for communication services continue to increase. Humans still want convenience in daily activities such as sending messages, video and voice, and want the quality of sending and receiving messages to be fast. This encourages telecommunications service providers to focus on innovative telecommunications networks to meet the needs of all customers. Research began by taking data at Tablue and AVS regarding the distance of the fiber cable used as far as 10Km from the OLT. Manual calculations using OTDR. The results of previous measurements and data processing regarding the attenuation obtained in fiber cables are followed by calculating the total attenuation using the existing formula. The next stage is data processing using RapidMiner software with the Naive Bayes algorithm. The final results of the comparison with this test method, namely the prediction results) show an accuracy value of 99.91%. Of the 1124 test data, 1080 data were predicted as OK sentiment and 43 data as Not OK. For prediction results from Not ok. and the Naive Bayes method shows an accuracy value of 0.962% OK. Not ok 0.038% of 1124, test data.
Keywords: Gigabit Passive Optical Network; Naive Byes; Fiber To The Home